2012
DOI: 10.3109/17453674.2012.688726
|View full text |Cite
|
Sign up to set email alerts
|

Survival of uncemented acetabular monoblock cups

Abstract: Background and purposeMonoblock acetabular cups represent a subtype of uncemented cups with the polyethylene liner molded into a metal shell, thus eliminating—or at least minimizing—potential backside wear. We hypothesized that the use of mono​block cups could reduce the incidence of osteolysis and aseptic loosening, and thus improve survival compared to modular designs.Patients and methodsWe identified all 210 primary total hip arthroplasty (THA) procedures in the Swedish Hip Arthroplasty Register that used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…While uncemented stems had a lower revision rate due to loosening they had a higher revision rate due to periprosthetic fracture in the first two postoperative years. Weiss et al 53 on the other hand reviewed the Survival of uncemented acetabular monoblock cups which represent a subtype of uncemented cups with the polyethylene liner molded into the metal shell and compared their survival to the modular designs in 210 hips from the Swedish Hip Arthroplasty Register. They concluded that both cups showed good survival rates at 11 years of follow up.…”
Section: Role Of Randomized Controlled Trials and Registry Datamentioning
confidence: 99%
“…While uncemented stems had a lower revision rate due to loosening they had a higher revision rate due to periprosthetic fracture in the first two postoperative years. Weiss et al 53 on the other hand reviewed the Survival of uncemented acetabular monoblock cups which represent a subtype of uncemented cups with the polyethylene liner molded into the metal shell and compared their survival to the modular designs in 210 hips from the Swedish Hip Arthroplasty Register. They concluded that both cups showed good survival rates at 11 years of follow up.…”
Section: Role Of Randomized Controlled Trials and Registry Datamentioning
confidence: 99%
“…The New Zealand registry reported revision rates per 100 observed component years of in total 10 501 uncemented monoblock cups (MoP and CoP articulations), which varied between 0.23 (95% confidence interval 0.06 to 0.59) and 0.64 (0.45 to 0.88) and which were similar to or slightly better than revision rates with uncemented modular variants (0.64 (0.50 to 0.81) to 0.76 (0.65 to 0.88), n=35 650). The Swedish Hip Registry reported a five year survival of 95% (91 to 98) of all 210 uncemented monoblock cups in the registry, which was similar to the survival of the chosen reference, which consisted of all 1130 most commonly used uncemented metal-backed cup designs implanted during the same period (five year survival 97% (96 to 98)) 25. The Finnish registry reported 100% survival of 136 implanted Morcher uncemented monoblock cups.…”
Section: Resultsmentioning
confidence: 60%
“…The Swedish Hip Registry reported a five year survival of 95% (91 to 98) of all 210 uncemented monoblock cups in the registry, which was similar to the survival of the chosen reference, which consisted of all 1130 most commonly used uncemented metal-backed cup designs implanted during the same period (five year survival 97% (96 to 98)). 25 The Finnish registry reported 100% survival of 136 implanted Morcher uncemented monoblock cups. One large US single-institutional survival registry (n=9584 total hip replacements, Mayo clinics) reported similar survivorship of in total 634 monoblock cups of three different brands after 4.7 to 8.2 years of follow-up when compared with the reference cup (Harris Galante).…”
Section: Resultsmentioning
confidence: 99%
“…The main purported disadvantage of this cup design is the lack of modularity, which rules out isolated liner exchange in cases involving early periprosthetic infections and after extended wear. Furthermore, assessment of proper cup seating due to the missing central screw hole is unfeasible with this cup design [ 26 ]. Coupled with the reasonable outcomes obtained using modular cups, these potential disadvantages of monoblock cups precluded their increased usage [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%